Inovasi Metode Pembelajaran untuk Meningkatkan Motivasi dan Pemahaman Siswa dalam Mempelajari Morfologi,Anatomi,dan Fisiologi Makhluk Hidup : Literature Review - Neli Permatasari; Hilda Mardiyana; Kurniasari Ambar; Kurniasari Sulistyorini; Rina Hidayati Pratiwi (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
The topics of morphology, anatomy, and physiology are integral to biology learning, yet they often present challenges for students due to their abstract and complex nature. Difficulties in understanding body structures and invisible biological processes lead to low student interest and engagement. This study aims to identify innovative learning approaches through an analysis of national scientific literature over the past decade. The results show that the integration of digital technology and student-centered learning methods can improve conceptual understanding and learning motivation. The most prominent innovations include the use of VR and AR-based media to clarify visualizations, the use of interactive videos and simulations to explain biological functions, and the application of contextual learning models such as Problem-Based Learning (PBL) and Project-Based Learning (PjBL). These approaches have proven effective in creating a more immersive learning experience that is relevant to students' needs.